PENGARUH VARIASI KEPOLARAN FASE GERAK ASETON-DIKLOROMETANA: METANOL-ASAM ASETAT TERHADAP % DISTRIBUSI (+)-KATEKIN DARI GAMBIR DENGAN METODE KROMATOGRAFI CAIR VAKUM - S.Y.,, Era; L, Eka; Widjaja, I.N.K. (Jurnal Farmasi Udayana, 2013)
The research was conducted to determine the influence of mobile phase polarity of acetone-dichloromethana : methanol-acetic acid on the percent distribution of (+)-catechin from gambier by vacuum liquid chromatography and to determine the polarity mobile phase required to obtain the largest amount of (+)-catechin percent distribution. Gambier extract was fractionated using vacuum liquid chromatography with several variations of polarity of acetone-dichloromethane : methanol-acetic acid mobile phase expressed by the dielectric constant value (?) of 13.74 to 17.51. Fractions were analyzed by TLC-spectrophotodensitometer to calculate the concentration and the percent distribution of (+)-catechin. To know the effect of variations in mobile phase polarity on the percent distribution of (+)-catechin performed statistical analysis using one-way ANOVA test (? = 0.05). The results show that the variation of polarity of acetone-dichloromethane : methanol-acetic acid mobile phase (? = 13.74 to 17.51) had a significant influence on percent distribution of (+)-catechin from gambier by vacuum liquid chromatography method (p <0.05). Fraction with a mobile phase of acetone-dichloromethane (4:6) 50% : methanol-acetic acid (3:4) 50%, which had a value of dielectric constant of 15.62 yield the largest amount of (+)-catechin percent distribution value (45.40%).
Keywords: (+)-catechin, gambier, VLC, polarity of mobile phase, dielectric constant